2012
DOI: 10.4103/0255-0857.93049
|View full text |Cite
|
Sign up to set email alerts
|

Detection and species identification of Campylobacter in stool samples of children and animals from Vellore, south India

Abstract: Campylobacter spp. are an important cause of bacterial gastroenteritis frequently isolated from animal, poultry and environmental samples. In this study, we investigated the zoonotic potential of Campylobacter spp. by comparing prevalence rates and species in 394 children with diarrhoea and 652 animals in Vellore using PCR-based tools. Eighteen children (4.5%) had campylobacteriosis, a majority of whom had co-pathogens (15/18) and most were infected with Campylobacter jejuni (16/18). A few C. coli and mixed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Mixed infections involving Campylobacter have been described previously; one large (n = 3,038) surveillance study of diarrhoea in hospitalised children <5 years of age in Bangladesh reported that 59% of all Campylobacter infections were associated with at least one other bacterial or protozoan pathogen [25]. Few studies have reported mixed infections of Campylobacter and viral pathogens; a cohort study in India demonstrated that rotavirus was associated with 11/18 Campylobacter infections in children <5 years of age [26]. Since data from in-vitro cell culture systems suggest that viral co-infection increases the adhesion and invasion of pathogenic Campylobacter species [27], further work should explore the clinical consequences of co-infection with viral enteric pathogens on the pathogenesis of Campylobacter infection.…”
Section: Discussionmentioning
confidence: 93%
“…Mixed infections involving Campylobacter have been described previously; one large (n = 3,038) surveillance study of diarrhoea in hospitalised children <5 years of age in Bangladesh reported that 59% of all Campylobacter infections were associated with at least one other bacterial or protozoan pathogen [25]. Few studies have reported mixed infections of Campylobacter and viral pathogens; a cohort study in India demonstrated that rotavirus was associated with 11/18 Campylobacter infections in children <5 years of age [26]. Since data from in-vitro cell culture systems suggest that viral co-infection increases the adhesion and invasion of pathogenic Campylobacter species [27], further work should explore the clinical consequences of co-infection with viral enteric pathogens on the pathogenesis of Campylobacter infection.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to these findings, many workers including Rajendran et al . [22] and Deckert et al . [23] have reported the higher presence of C. jejuni than C. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacteriosis has also been reported to be most prevalent in children under the age of 5 years in this region (isolated in 10% of cases, compared to 3.7% for other age groups; P Ͻ 0.001) (63). In Vellore, South India, between January 2003 and May 2006, 4.5% of 349 children under the age of 5 years with diarrhea were positive by PCR for C. jejuni or C. coli (65). In addition, in a prospective case-control study conducted between 1 December 2007 and 3 March 2011 to identify the etiology of diarrhea in children aged 0 to 59 months, C. jejuni was reported to be significantly associated with moderate to severe diarrhea in children from Kolkata, India, Mirzapur, Bangladesh, and Karachi, Pakistan (66).…”
Section: Epidemiologymentioning
confidence: 96%